Relationship between physical characteristics and competitive performance of under-12 and 14-year-old elite boy and girl tennis players - Dobos, K.; Nagykaldi, C. (Trends in Sport Sciences, 2016)
Introduction: The role of physical abilities in modern tennis is gradually increasing, and gathering accurate information about the relationship between the physical abilities and competition performance of tennis players may help us objectively judge the role of physical abilities in competition performance, and create the possibility of forming optimal conditional training programmes. Aim of Study: The aim of the research was: 1) to examine the relationship between competition performance (player`s place on the ranking list) and conditional abilities in the under-12 and -14-year-old elite boy and girl tennis players; and 2) to make suggestions - on the basis of gathered data - for the characteristics of physical training of players at this age. Material and Methods: Altogether 80 elite junior tennis players took part in the study. Eleven field tests were used to assess their physical ability: hexagon test; 5 m run; standing long jump; overhead medicine ball toss; overhead ball throw; speed of the serve; push-ups in 30 s; 5 × 10 m shuttle run; spider run; sit and reach; and shoulder turning with a stick. Results: A correlation with the position on the rankings could be found in the standing long jump (r = -0.54), 5 m run (r = 0.51), speed of serve (r = -0.52) and in push-ups in 30 seconds (r = -0.45) in the under-12-year-old girls; and in the standing long jump (r= -0.63), push-ups in 30 seconds (r = -0.58), and 5 × 10 m shuttle run (r = -0.56) in the under-14-year-old girls. However, there was no correlation between the physical characteristics and competition performance of the under-12 and-14-year-old-boy players. Conclusions: The results verified the statement that the competition performance of under-12 and -14-year-old tennis players cannot be characterized either with some physical variables, as tennis is a tactically and technically dominant ball game requiring open skills, and differentiation in conditional training according to gender already at this age is necessary.